Analysis Of Walking Accessibility To Rapid Penang Bus Services (Route 303) In Penang Island - Zauki, Wan Nadhira Shaqina Wan (Universiti Sains Malaysia, 2017)
This study was conducted to investigate the walking accessibility of pedestrian toward the Rapid Penang bus services in Penang Island. In this study, several parameters such as socio-demographic, walking distance, time travel and satisfaction level of users were examined to determine the significant factors that influence the walking accessibility toward public bus services. Within two weeks period, the questionnaire surveys of 400 respondents were recorded for this study. The collected data were analysed using descriptive analysis and statistical analysis through Statistical Package for the Social Science (SPSS). Multiple regression analysis was used in statistical analysis to determine factors that significantly influenced pedestrian willingness to walk to access the public bus services according to current environmental and infrastructure condition and also the future improvement of the environmental and infrastructure condition. From the results acquired through the multiple regression analysis, type of bus stops, socio-demographic, distance of walking, time of walking, the satisfaction level of users and trip purpose were factors that contribute to pedestrian willingness to walk to access the public bus services. Besides that, the outcome of this study also had identified the maximum, minimum and average distance walked by the pedestrian to reach the bus stops as well as the time travel taken.